The physiology of yoga - McGonigle, Andrew; Huy, Matthew P. 1979-
"This book explains how each of the body's internal systems is affected and enhanced by a consistent yoga practice. It allows the serious or curious yogi to better understand how yoga provides myriad benefits for the body and mind. It also encourages readers to engage in critical thinking when evaluating claims about what yoga can do. Chapters cover the musculoskeletal, nervous, respiratory, cardiovascular, lymphatic, immune, endocrine, reproductive, and digestive systems of the body. A final chapter provides practical application with four sample yoga practices"--
"While many people practice yoga simply because it helps them feel good, the physiological basis for yoga's effects on the body and mind is often unknown or misunderstood. Understanding these physiological concepts can help to deepen your yoga practice.The Physiology of Yoga separates speculation from fact by examining how the body responds and adapts to yoga within many systems of the body: musculoskeletal, nervous, respiratory, cardiovascular, lymphatic, immune, endocrine, reproductive, and digestive. Straightforward explanations guide you in sorting through conflicting information about what yoga really can help you achieve and in evaluating whether certain yoga methods provide benefits to any or all of those systems.You can experiment with concepts through Try It Yourself sidebars, which focus on mindful movement, meditation, and breathing. The 14 Myth or Fact sidebars explore popular claims about yoga, such as whether a shoulder stand can stimulate the thyroid or if twists can detoxify the liver. You'll get the most current research to determine the validity of various claims so you can avoid practices that could be harmful or counterproductive and can decide for yourself what works for your practice.Finally, experience firsthand how yoga affects your physiology by exploring specific yoga poses and four sequences. Each sequence explains which of the physiological principles from the earlier chapters may be most prevalent in that sequence.With The Physiology of Yoga, you or your students can navigate all the conflicting views and opinions about the impact of yoga and learn to practice yoga while fully enjoying the benefits of mindful movement.CE exam available! For certified professionals, a companion continuing education exam can be completed after reading this book. The Physiology of Yoga Online CE Exam may be purchased separately or as part of The Physiology of Yoga With CE Exam package that includes both the book and the exam"--
Machine generated contents note: Chapter 1. musculoskeletal system -- Bone -- Joints -- Muscles -- Cartilage -- Tendons, ligaments, and aponeuroses -- Fascia -- The science of stretching and flexibility -- Pathologies, injuries, and conditions -- Conclusion -- Chapter 2. nervous system -- Cells of the nervous system -- Central nervous system -- Peripheral nervous system -- Nervous system conditions -- Conclusion -- Chapter 3. respiratory system -- Anatomy and physiology of the respiratory system -- The biomechanics of quiet breathing -- All about the diaphragm -- Forced exhalation and inhalation -- Atmospheric air and expelled air -- Good, wholesome oxygen? -- Ujjayi breathing -- Nose breathing and mouth breathing -- The psychological and physiological effects of pranayama and slow breathing -- Pathologies and conditions of the respiratory system -- Conclusion -- Chapter 4. cardiovascular system -- Blood -- Heart -- Circulation -- Role of the cardiovascular system in maintaining homeostasis -- Resting heart rate and cardiac output -- Heart rate variability -- Blood pressure -- Cardiovascular conditions -- Conclusion -- Chapter 5. lymphatic and immune systems -- Lymphatic system -- Immune system -- Conclusion -- Chapter 6. endocrine system -- What Is a hormone? -- Cortisol: the master hormone -- Insulin -- Thyroid hormones -- Endorphins: our body's morphine -- Dopamine -- Pathologies -- Conclusion -- Chapter 7. reproductive system -- Female reproductive system anatomy -- Female reproductive system physiology -- Male reproductive system -- Reproductive system conditions -- Conclusion -- Chapter 8. digestive system -- Anatomy and physiology of the digestive system -- Diet and the digestive system -- Pathologies and gastrointestinal problems -- Conclusion -- Chapter 9. practice with confidence -- Strong, dynamic practice -- Slow hatha practice -- Chair yoga practice -- Restorative yoga practice -- Conclusion.
MS Salazar (Recommending faculty) AY2022-2023
Includes bibliographical references (pages 214-242) and index.
Keywords: Yoga -- Physiological aspects; HEALTH & FITNESS / Yoga; BODY, MIND & SPIRIT / Mindfulness & Meditation